2018
DOI: 10.1016/j.wneu.2018.03.194
|View full text |Cite
|
Sign up to set email alerts
|

Petrous Face Meningiomas: Classification, Clinical Syndromes, and Surgical Outcomes

Abstract: PFMs present with distinct clinical syndromes based on their location along the petrous face: anterior with trigeminal symptoms, middle with auditory/vestibular symptoms, and posterior with symptoms of mass effect/hydrocephalous. Surgical resection is associated with excellent long-term survival and a low rate of recurrence, which can be managed with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Hearing impairment after treatment was common, with 30% to 35% of respondents reporting moderate or more severe loss in the tumor ear, which is consistent with the 30% to 40% rate of hearing complication cited in previous studies (24,25). Although about one-third of patients can present with hearing loss at the time of diagnosis (6,15), the majority of patients in this study reported normal hearing bilaterally before treatment. In the petroclival meningioma cohort, four patients underwent translabyrinthian resection, which obligates postoperative deafness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hearing impairment after treatment was common, with 30% to 35% of respondents reporting moderate or more severe loss in the tumor ear, which is consistent with the 30% to 40% rate of hearing complication cited in previous studies (24,25). Although about one-third of patients can present with hearing loss at the time of diagnosis (6,15), the majority of patients in this study reported normal hearing bilaterally before treatment. In the petroclival meningioma cohort, four patients underwent translabyrinthian resection, which obligates postoperative deafness.…”
Section: Discussionsupporting
confidence: 89%
“…Posterior fossa meningiomas are a heterogenous collection of tumors that can have varying outcomes depending on the predominant location of the tumor. There have been multiple classification schemes proposed to associate tumor position with clinical symptoms and treatment outcomes (3)(4)(5)(6). All of these classification schemes have separated tumors arising from the cerebellopontine angle from tumors arising in the petroclival region.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the central site of dural attachment, cerebellopontine angle meningiomas were classified into three types ( 6 ): anterior tumors were those that originated from the tentorium cerebelli or the petrous bone dura anterior the internal auditory canal; middle tumors were those that originated from the dura mater in the internal auditory canal; posterior tumors were those that originated from the sigmoid and transverse sinuses or the petrous bone dura posterior the internal auditory canal ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…True “clival meningiomas” originate from a broad attachment to the median upper two-thirds of the clivus, and petroclival meningiomas are described as tumors in which the dural attachment is located at the upper two-thirds of the clivus, lateral to the midline, at the level of the petroclival junction, and medial to the trigeminal nerve [ 103 ]. Over the years, several classifications arose to warrant different surgical routes aimed at maximizing surgical outcomes while restraining complications [ 104 , 105 , 106 , 107 ]. The main approaches described in the pertinent literature rely on the anterolateral, lateral, and posterolateral corridors ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%